Efektivitas Media Edukasi Gizi terhadap Pengetahuan dan Kepatuhan Diet pada Lansia dengan Hipertensi: Studi Literatur. - Eka Devi Aryanti; Eka Andriani; Dwikani Oklita Anggiruling (Media Gizi Kesmas, 2026)
Background: Hypertension remains a major health concern among the elderly in Indonesia, with prevalence reaching 57.8%–64.0% according to the 2023 Indonesia Health Survey. Nutrition education media have been widely applied to improve Knowledge, Attitude, and/or Practice (KAP) among hypertensive elderly, yet comprehensive synthesis across different media types remains limited. Objectives: This study aims to examine the role of nutrition education media on KAP among hypertensive elderly. Methods: This literature review was guided by the PRISMA framework. Data were obtained from Google Scholar, Garuda, and PubMed. Ten studies published between 2021 and 2026 met the inclusion criteria. Methodological quality was assessed using the JBI Critical Appraisal Checklist for Quasi-Experimental Studies. Results: Nine of the ten studies reported significant improvements in knowledge following nutrition education, consistent across print, audiovisual, digital, and demonstration-based media. Attitude and practice were measured in only two studies each, and appeared more responsive to interactive media such as audiovisual and demonstration tools. The mean quality appraisal score was 78%, with the main limitation being the absence of an independent control group in nine of the ten studies. Conclusion: Nutrition education media play a varying role across KAP domains among hypertensive elderly, with knowledge being the most consistently improved domain, while attitude and practice require more interactive approaches.